1988
DOI: 10.1055/s-2007-1025024
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Physical Activity, Strenuous Exercise, and Salivary Immunoglobulin A Levels in Young Adults: The Amsterdam Growth and Health Study

Abstract: Secretory IgA (S-IgA) levels in stimulated salvia were measured before and after a maximal treadmill test in a population of 175 young adults (84 men, 91 women). Habitual physical activity levels of this population were measured by a standardized interview, and scores were obtained for the amount of time and intensity of sports activities and total activity. Before the maximal treadmill test, men and women showed no statistically significant differences in the salivary concentrations of S-IgA, but the concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…However, in a recent study, Winzer et al (1999) have shown that a period of acute exercise elicits an increase in both [IgA s ] and IgA secretion rate. On the other hand, early studies by Schouten et al (1988) and Karper and Goldfarb (1995) found no conclusive evidence that moderate exercise positively affects humoral immunity, and Nehlsen-Cannarella et al (1990) reported that subjects in their exercise group did not express any significant differences in concentrations of IgA or other serum immunoglobulins. Recently, Fahlman et al (2000) examined the effects of a similar 10 week endurance training programme, similar to that used in the present study, to examine immune function in elderly women.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, in a recent study, Winzer et al (1999) have shown that a period of acute exercise elicits an increase in both [IgA s ] and IgA secretion rate. On the other hand, early studies by Schouten et al (1988) and Karper and Goldfarb (1995) found no conclusive evidence that moderate exercise positively affects humoral immunity, and Nehlsen-Cannarella et al (1990) reported that subjects in their exercise group did not express any significant differences in concentrations of IgA or other serum immunoglobulins. Recently, Fahlman et al (2000) examined the effects of a similar 10 week endurance training programme, similar to that used in the present study, to examine immune function in elderly women.…”
Section: Discussionmentioning
confidence: 94%
“…Mackinnon (1996) reports that the IgA class of antibodies primarily interact and defend the various secretory surfaces from invasion; therefore, [IgA] can readily be measured in tears, saliva, or fluids from the respiratory, genito-urinary and gastro-intestinal tracts. Although heavy exercise has been shown to decrease markedly the IgA concentrations of both nasal and salivary ([IgA s ]) samples (Tharp and Barnes 1989;Mackinnon and Jenkins 1993), the few studies that have examined the effects of moderate exercise on [IgA s ] have been inconclusive (Schouten et al 1988;Nehlsen-Cannarella et al 1990;Karper and Goldfarb 1995;Mitchell et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…43 Maximal intensity exercise elicits post-exercise decreases in the concentration of IgA in competitive cyclists 11,13 and in groups of recreational male athletes. 7,47,48 In contrast, increased concentrations of IgA have been reported in a study of male recreational athletes after maximal intensity exercise, 49 in marathon runners after a standard 42 km race 9 and in a moderately exercising group of runners and game players. 5 The concentration of salivary IgA was unchanged in a study of well-trained team game players.…”
Section: Salivary Igamentioning
confidence: 90%
“…A decrease in absolute concentrations of salivary IgA has been reported for elite skiers, 43 swimmers, 4,5 distance runners 44 and cyclists. 11,13 In squash players, the response of 13 8 Male cyclists Decreased absolute concentrations Mackinnon et al (1989) 11 Decreased as a proportion of total protein after a 2 h exhaustive cycle ergometer test Schouten et al (1988) 49 175 Young adults Decreased after maximal treadmill test in females, increased after maximal treadmill test in males Tharp and Barnes (1990) 4 21 Swimmers Decreased after routine training session Cameron and Priddle (1990) 44 13 Distance runners Decreased after 10.5 km high-intensity run Mackinnon et al (1992) 20 12 Female hockey players Decreased proportion relative to total protein after each training session and competition 7 29 Young males Decreased after maximal treadmill running 48 24 Young males Decreased after submaximal treadmill running 46 8 Male kayakers Decreased secretion rate after each training session Mackinnon and Jenkins (1993) 47 12 Young males Decreased output after brief supramaximal interval cycling Mackinnon and Hooper (1994) 23 10 Joggers Decreased after moderate treadmill exercise 8 Distance runners 5 26 Swimmers Decreased after routine training sessions in swimmers 12 Controls…”
Section: Salivary Igamentioning
confidence: 99%
“…For example, it has been shown (although with a maximal treadmill protocol) that males exhibited an acute increase in salivary s-IgA post-exercise whereas females exhibited a decrease (Schouten et al 1988). Hence, the difference between the present findings, with all male subjects, and the exercise-induced decrease observed by Fahlman et al (2001) may be explained by the fact that the subjects in the latter study were all female.…”
Section: Discussionmentioning
confidence: 99%